MIND THE GAP: ALIGNING INFORMATION TECHNOLOGY WITH THE BUSINESS STRATEGY - Pellissier, Ren (The South African Journal of Industrial Engineering, 2011)
Business organizations engage in strategic planning sessions in order to become more compet itive in the chan ging markets, However, despite evidence to the contrary, they do not seem to realize the grow ing value of information and technology in achieving this. Rarely do business organizations reali ze the need for strategic IT planning, and more over , alignment of the busines s and IT strategies in one synergistic, cohesive whole . This paper explores the evolution of IT as competitive medium and as center for growth, innovation and radical change, The notion of IT centered organizations over and above IT as support or enabling function is discussed, It is maintained that organizations that do not deal with the above, that stay in flux or believe in incremental change , will not remain competitive and will be lost in the Information world.